Use of heart-rate variability to examine readiness to perform in response to overload and taper in swimmers - Bulte, K. R.; Bruce, L.; Hammond, K.; Corrigan, S. L.; Main, L. C. (International Journal of Sports Physiology and Performance, 2025)
Context: The lack of consensus on the best approach to assess the fatigue and readiness status of swimmers has led to an increased risk of maladaptation, overtraining, and suboptimal readiness to perform. Subjective athlete monitoring is prominent in swimming but is prone to bias, distortion, and misinterpretation. Heart-rate variability (HRV) has gained attention from swimming practitioners as an objective monitoring tool for assessing physiological status.